OPTIMASI PEMBANGKIT LISTRIK TENAGA ARUS LAUT MENGGUNAKAN SISTEM TURBIN SAVONIUS TERMODIFIKASI - Rahmi L, Halida; Dharmala S, Budi; Gediana, Almas; Yusup, Agus; Septria, Wenty (BERKALA FISIKA, 2015)
Difficulty of access to service and installation of the electrical network in the area around a coast becomes a factor causing uneven distribution of power network. Therefore, a new prototype of Sea Flow Power Plant was prepared using a modified Savonius turbine. The modified Savonius turbine is a vertical wind turbine, which is modified into a horizontal turbine and made two pairs of turbines in different directions. Advantage of this turbine can optimally capture the come and back flows. Preparing prototype of the turbine is conducted after collecting data of the sea flow velocity surrounding Teluk Penyu - Cilacap, that is followed by manufacturing a modified Savonius turbine and prototype of PLTAL. Performance test reveals that the prototype can generate P =0,3 Watt, the velocity of turbine rotation ω = 44.42 rad/s, the turbine torque M = 0,0064 Nm and the diameter of turbine d = 0,32 m.  The sea flow velocity is often naturally changed leading to the turbine rotation change. It is found that the power and the turbine rotation increase with increasing the sea flow velocity.  At the sea flow velocity of  1,5 m/s, the prototype of PLTAL has good performance and very potential as a source of alternative electrical energy in the future. Keywords: Savonius turbine,  sea flow, electrical energy, power plant.